2022
DOI: 10.3390/molecules27061821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salinity Stress on Color Parameters, Leaf Pigmentation, Polyphenol and Flavonoid Contents, and Antioxidant Activity of Amaranthus lividus Leafy Vegetables

Abstract: This is the first attempt to evaluate the impact of four salinity levels on the color parameters, pigments, polyphenols, flavonoids, and antioxidant capacities of four promising A. lividus genotypes. The color parameters, such as the yellowness/blueness (b*) and the chroma (C*); the antioxidant components, such as the polyphenols and flavonoids; and the antioxidant capacities of the leaves were remarkably increased by 39, 1, 5, 10 and 43%, respectively, at 50 mM of NaCl, and by 55, 5, 60, 34, 58 and 82%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 59 publications
3
40
0
Order By: Relevance
“…Sarker and Oba [ 150 , 161 ] detected a parallel tendency. Positive and significant correlations were observed with ascorbic acid, TP, AP (DPPH), TF, β-carotene, and AP (ABTS + ), which was corroborative to past results on salt-induced amaranth [ 218 , 219 , 220 , 221 , 222 ]. The positive and noteworthy correlations of ascorbic acid, AP (DPPH), TP, β-carotene, TF, and AP (ABTS + ) suggested that β-carotene, TF, ascorbic acid, and TP had strong AP.…”
Section: Resultssupporting
confidence: 90%
“…Sarker and Oba [ 150 , 161 ] detected a parallel tendency. Positive and significant correlations were observed with ascorbic acid, TP, AP (DPPH), TF, β-carotene, and AP (ABTS + ), which was corroborative to past results on salt-induced amaranth [ 218 , 219 , 220 , 221 , 222 ]. The positive and noteworthy correlations of ascorbic acid, AP (DPPH), TP, β-carotene, TF, and AP (ABTS + ) suggested that β-carotene, TF, ascorbic acid, and TP had strong AP.…”
Section: Resultssupporting
confidence: 90%
“…The increment of pigment displayed a drastic decline in TC and β-carotene. Significant positive relationships of β-carotene and TC with TP, TA (ABTS + and DPPH), and TF recommended that β-carotene and TC displayed a strong capacity to quench radicals which were corroborative of the previous amaranths [ 81 , 82 , 83 ]. β-carotene and TC were associated positively among them.…”
Section: Resultssupporting
confidence: 66%
“…Highly significant ANOVA for all the parameters was observed, which indicated the preponderance of genetic variations across the genotypes and justified the inclusion of the genotypes for a combining ability study. A wide range of variability was also reported in different mungbean genotypes [11][12][13]29], rice germplasm [36][37][38], maize [39], and other crops [40,41]. The analysis of variance (Table 1) shows highly significant variations among the parents and offspring for all the studied characters indicating the presence of genetic variability in the material under study.…”
Section: Analysis Of Variance (Anova) For Combining Abilitymentioning
confidence: 70%